2021
DOI: 10.1155/2021/1009231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pathogen Type on Neonatal Sepsis Biomarkers

Abstract: Understanding immunoregulation in newborns can help to determine the pathophysiology of neonatal sepsis and will contribute to improve the diagnosis, prognosis, and treatment and remains an urgent and unmet medical need to understand hyperinflammation or hypoinflammation associated with sepsis in newborns. This study included infants (up to 4 days old). The “sepsis” criteria was a positive blood culture. C-reactive protein demonstrates a strong dependence on the pathogen etiology. Therefore, its diagnostic odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These results were comparable to pervious results reported by Akhmaltdinova et al (2021) and Hanaganahalli et al, (2018), who showed significant differences in CRP results between the patients and control group. Liu et al, (2019) evaluated the diagnostic value of the CRP test in detecting neonatal septicemia, and suggested that the CRP test has a good diagnostic marker for neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…These results were comparable to pervious results reported by Akhmaltdinova et al (2021) and Hanaganahalli et al, (2018), who showed significant differences in CRP results between the patients and control group. Liu et al, (2019) evaluated the diagnostic value of the CRP test in detecting neonatal septicemia, and suggested that the CRP test has a good diagnostic marker for neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Thirty studies were included in our systematic review and meta-analysis [ 17 – 46 ]. Of them, 15 studies had a control group of healthy neonates [ 19 , 24 27 , 29 , 30 , 32 , 33 , 35 – 39 , 46 ], five studies had a control group of neonates who were suspected of sepsis, but eventually had negative blood cultures [ 20 , 28 , 40 , 41 , 44 ], and ten studies included other ICU admitted neonates as the control group [ 17 , 18 , 21 23 , 31 , 34 , 42 , 43 , 45 ]. Twenty studies were prospective [ 17 25 , 27 , 29 , 30 , 32 , 35 – 38 , 41 , 42 , 44 ] and 10 studies were retrospective [ 26 , 28 , 31 , 33 , 34 , 39 , 40 , 43 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the pathophysiology of sepsis, there will be an alteration in the coagulation cascade, which will allow the release of multiple pro-and anti-inflammatory cytokines, leading to thrombus formation [ 32 ]. This will cause fibrinolytic and fibrinogenic substances to be depleted, leading to further platelet destruction.…”
Section: Discussionmentioning
confidence: 99%